2006
DOI: 10.1177/0269881106068289
|View full text |Cite
|
Sign up to set email alerts
|

Is clozapine—aripiprazole combination a useful regime in the management of treatment-resistant schizophrenia?

Abstract: Around 40-70% patients with treatment-resistant schizophrenia fail to respond to clozapine. Though combining antipsychotics is commonly practised with non-responders, there is little evidence for its use.We carried out a retrospective review of case notes of patients with treatment-resistant schizophrenia on clozapine-aripiprazole combination at our clozapine clinic. We report changes in psychotic symptoms, social function, weight, total cholesterol, serum glucose, HDL, CGI and GAF score pre- and post-aripipra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…It is possible that some of them could have benefited by switching over to clozapine or clozapine augmentation. 22,23 However, studies on the use of clozapine augmentation remain inconclusive. Meta-analyses looking at clozapine augmentation with antipsychotics for treatment-resistant schizophrenia have arrived at differing conclusions.…”
Section: 10mentioning
confidence: 99%
“…It is possible that some of them could have benefited by switching over to clozapine or clozapine augmentation. 22,23 However, studies on the use of clozapine augmentation remain inconclusive. Meta-analyses looking at clozapine augmentation with antipsychotics for treatment-resistant schizophrenia have arrived at differing conclusions.…”
Section: 10mentioning
confidence: 99%
“…Aripiprazole is a potent (high-affinity) partial agonist at D2 27 and 5-HT1A receptors and a potent antagonist at 5-HT2A 28 receptors. In a study of 24 patients with treatment resistant schizophrenia who had aripiprazole added to decreased doses of clozapine, Karunakaren et al 29 reported an average weight loss of 5.1 kg over 34 weeks. A 6-week open-label trial to examine the effects of adjunctive aripiprazole in ten clozapine-treated subjects observed a significant decrease in weight (from 219.4 ± 40.0 lbs to 213.7 ± 38.3 lbs) and triglycerides (from 274 ± 229 to 176 ± 106 mg/dL) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…However, two cases of dyskinesia and malignant neuroleptic syndrome were reported in a sample of 26 patients [32].…”
Section: Discussionmentioning
confidence: 99%